2011
DOI: 10.1097/qai.0b013e31820b07ab
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Gamma Release Assays for the Diagnosis of Latent Tuberculosis Infection in HIV-Infected Individuals: A Systematic Review and Meta-Analysis

Abstract: OBJECTIVE-To determine whether interferon-gamma release assays (IGRAs) improve the identification of HIV-infected individuals who could benefit from LTBI therapy. DESIGN-Systematic review and meta-analysis.METHODS-We searched multiple databases through May2010 for studies evaluating the performance of the newest commercial IGRAs (QuantiFERON-Gold In-tube [QFT-GIT] and T-SPOT. TB [TSPOT])in HIV-infected individuals. We assessed the quality of all studies included in the review, summarized results in pre-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
182
4
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(199 citation statements)
references
References 42 publications
6
182
4
7
Order By: Relevance
“…Although IGRAs are more sensitive and specific than TST in persons without HIV infection (6), a change from positive to negative results within both short and long-term periods were observed in PLWHIV with no or low TB risk (7,8). A meta-analysis of studies assessing TST and IGRA for LTBI screening among HIV-infected individuals demonstrated comparable performance between both tests (2). However, significant heterogeneity was noted among the studies included in this metaanalytic reports.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although IGRAs are more sensitive and specific than TST in persons without HIV infection (6), a change from positive to negative results within both short and long-term periods were observed in PLWHIV with no or low TB risk (7,8). A meta-analysis of studies assessing TST and IGRA for LTBI screening among HIV-infected individuals demonstrated comparable performance between both tests (2). However, significant heterogeneity was noted among the studies included in this metaanalytic reports.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant heterogeneity was noted among the studies included in this metaanalytic reports. In addition, the outcomes evaluated the predictive value of IGRA for active TB development and IGRA sensitivity in individuals using culture confirmation of active TB in comparison with TST (2). More longitudinal studies evaluating IPT efficacy based on positive TST, with or without IGRA testing in PLWHIV from high-endemic TB countries, are needed for evidence-based treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pulmonary Medicine 5 seems to be slightly less affected by immunosuppression (19). However, only five studies compared their sensitivity head to head (32)(33)(34)(35)(36), with only one study showing Quantiferon GIT QFT-GIT with a greater sensitivity than T-SPOT.TB in PLWHA (36). A prospective study from Iran (by Mardani et al) compared TST and Quantiferon TB gold in 50 HIV positive patients.…”
Section: A) Immunosuppressed Patientsmentioning
confidence: 99%
“…We selected T-SPOT because this method has higher sensitivity in immunosuppressive conditions (Komiya et al 2010;Cattamanchi et al 2011) and requires less blood volume. At least 5 ml of venous blood was collected into a heparinized blood-collecting tube which was performed along with blood cell count and biochemical examination, and the blood samples were outsourced for the assay.…”
Section: Interferon-gamma Release Assay (Igra)mentioning
confidence: 99%